1997
DOI: 10.1007/s003300050230
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous recanalization of acutely thrombosed vessels by hydrodynamic thrombectomy (Hydrolyser)

Abstract: A hydrodynamic thrombectomy catheter was prospectively evaluated for the treatment of recently thrombosed vessels. A total of 52 consecutive patients (42 males and 10 females; mean age 64 +/- 15 years) presenting with acute or subacute occlusion of dialysis shunts (n = 25), peripheral bypass (n = 14) or native arteries (n = 15) were treated with the Hydrolyser (Cordis Europa NV, Roden, The Netherlands). Mean occlusion time was 4 days (range 1-17 days) and mean thrombus length 19 +/- 11 cm. The Hydrolyser was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…On the basis of prior experience with similar thrombus aspiration devices and the results of nonrandomized trials with the current catheter, it was likely that this hydrodynamic thrombectomy system would be at least as effective as pulse-spray thrombolysis in removing fresh thrombus from hemodialysis grafts (12,21). It was also expected that the time to effectively remove the graft thrombus would be shorter than that with thrombolysis owing to the lack of dwell time (12,13,21). Both expectations were met.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the basis of prior experience with similar thrombus aspiration devices and the results of nonrandomized trials with the current catheter, it was likely that this hydrodynamic thrombectomy system would be at least as effective as pulse-spray thrombolysis in removing fresh thrombus from hemodialysis grafts (12,21). It was also expected that the time to effectively remove the graft thrombus would be shorter than that with thrombolysis owing to the lack of dwell time (12,13,21). Both expectations were met.…”
Section: Discussionmentioning
confidence: 86%
“…Now several thrombectomy techniques have been introduced clinically or are in trials (4,(7)(8)(9)(10)(11)(12)(13)(14). They promise faster and more efficient thrombus removal, do not subject the patient to the risks of thrombolytic therapy, and apply also to those patients who are not candidates for lysis.…”
Section: Resultsmentioning
confidence: 98%
“…In addition many occlusions are caused by an underlying plaque and/or thrombus, so the ideal thrombectomy device should also be capable of removing organized thrombus [3,16]. Data for MT using rotational recirculation devices which work by the vortex principle or hydrodynamic (rheolytic) recirculation devices report success rates in the lower extremity arteries of 66-90% [1,[7][8][9][17][18][19]; however, adjunctive thrombolysis (usually overnight) was required in 20-42% of cases [1, 7-9, 17, 18]. Rousseau et al reported success for MT alone in 61% of their cases, which was increased to 83% by adding thrombolytic therapy [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…Data for MT using rotational recirculation devices which work by the vortex principle or hydrodynamic (rheolytic) recirculation devices report success rates in the lower extremity arteries of 66-90% [1,[7][8][9][17][18][19]; however, adjunctive thrombolysis (usually overnight) was required in 20-42% of cases [1, 7-9, 17, 18]. Rousseau et al reported success for MT alone in 61% of their cases, which was increased to 83% by adding thrombolytic therapy [1,17]. Morgan and Belli [1] concluded that mechanical thrombectomy devices are useful for the treatment of thrombosed dialysis grafts but less effective in native arteries and bypass grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical or percutane ous mechanical thrombectorny [7] of the pa tient's graft should be performed to increase flow across, and help maintain patency of, the stented region. In our particular situation, the re A rterial access is typically ob tamed through the common fern oral artery or the brachial artery in patients whose coagulation profiles are near normal.…”
Section: Discussionmentioning
confidence: 99%